The orbit of Aegaeon and the 7:6 Mimas-Aegaeon resonance - Callegari, Nelson [UNESP]; Rodríguez, Adrián (Springer Nature, 2023)
Aegaeon (S/2008 S 1) is the last satellite discovered by the Cassini spacecraft at the end of the 2000 s. Like the satellites Methone and Anthe, it is involved in mean motion resonance with the mid-sized Mimas. In this work, we give a detailed analysis of the current orbit of Aegaeon identifying the resonant, secular and long-term perturbations due to Mimas and the oblateness of Saturn, and the effects of Tethys. For this task, we perform thousands of numerical simulations of full equations of motion of ensembles of small bodies representing clones of Aegaeon. We have mapped the domain of the 7:6 Mimas-Aegaeon resonance in the phase space of the semi-major axis and eccentricity. It displays a large area dominated by regular motions associated with the 7:6 corotation resonance surrounded by chaotic layers. Aegaeon is currently located very close to the periodic orbit of the resonance, which extends up to eccentricities ∼ 0.025 centered at semi-major axis ∼ 168 , 028 km. We show that the current orbit of Aegaeon has an important forced component in eccentricity due to the 7:6 resonance. The orbital inclination of Aegaeon has a non-negligible forced value due to long-term perturbations of Mimas. These two forced modes explain the complex perturbed orbit of Aegaeon without requiring the co-existence of multiple resonances.
Keywords: Aegaeon; Celestial Mechanics; Dynamics of Natural Satellites; Saturnian system